The Logical Function Analysis on the Thread about Vaccines in Social Media Twitter - Nicky Hasrimarta; Yuli Tiarina (English Language and Literature, 2022)
In logical function analysis, the analysis deals with clause complexes form which is the meaning relation of each clause in the clause complex. This thesis is about the logical function analysis used in the thread about vaccines in social media twitter. The objective of this research is to find out the types of logical function analysis in the threads about vaccines which is in clause complexes form. This research is conducted by qualitative descriptive approach which means this research makes the description of the situation. The data of this research is from the thread 1 about vaccine by Prof. Christine Pagel on her twitter account. The thread consists of 10 tweets that are 35 clause complexes. And the other data is from the thread 2 by Nida Qadir, MD on her twitter account. The thread consists of 5 tweets that are 21 clause complexes. The finding of this research is indicated that there are 2 main types of logical function; expansion and projection. In analyzing thread 1, there were 19 elaboration, 3 extension, 12 enhancement, and 1 types of idea. There is no locution type in thread 1. In analyzing the thread 2, there are 9 elaboration, 3 extension, 7, enhancement, 1 locution, and 1 idea.